FACTORS AFFECTING DIVIDEND PAY OUT RATIO WITH ROE (RETURN ON EQUITY) AS MODERATING VARIABLE - Hastuti, Rini Tri; Andrew, Richard (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to find out whether cash ratio and ATO (asset turnover) have an influence on dividend pay-out ratio by using ROE (return on equity) as a control variable or moderating variable in the manufacturing industry listed on the Indonesia Stock Exchange during the 2018-2020 period. Samples were taken using purposive sampling method, and the data obtained were 39 firms. The data is processed using statistical software applications to analyze into multiple regression equations, namely the EViews program version 12 and Microsoft Excel 2010. This study provides test results that cash ratio and ATO (asset turnover) have an insignificant negative effect on dividend pay-out ratio. ROE (return on equity) cannot moderate cash ratio on dividend pay-out ratio. But ROE (return on equity) can moderate ATO (asset turnover) on dividend pay-out ratio. The conclusion of this study can analyze the factors that influence firm performance in increasing dividend pay-out ratio so that investors are interested in investing.